Explorative study, a journey to discover - Zuliani Arango, Liliana (Investigación y Educación en Enfermería, 2010)
<!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> This article talks about the journey the author starts with the encouragement to discover the theoretical and methodological knowledge importance to make an explorative study which allows making a bibliographic and argumentative review about the different types of research, the methodological perspectives and the tools and techniques used to collect information; information that is complemented with the interview to one of the actors who have participated in the health policies construction being able to reflect about the Me researcher. It is the starting point of a journey which destination will be to discover and learn.